# Use the quadratic formula to solve the following equation. (r-3)(r+9)=-9?

(r-3)(r+9)=-9

### 4 Answers

Relevance
• Rogue
Lv 7
7 years ago
Favorite Answer

(r − 3)(r + 9)=-9

=> r(r + 9) −3(r + 9)= -9

=> r^2 + 9r −3r − 27 = -9

=> r^2 + 6r − 18 = 0

now that you have in the form of ax^2 + bx + c = 0 you can use the quadratic formula x = [-b ±√(b^2 − 4ac)]/(2a) in this case a = 1, b = 6, and c = -18

=> x = [-6 ±√(6^2 − 4*1*-18)]/(2*1)

=> x = [-6 ±√(36 +72)]/2

=> x = [-6 ±√(36 * 3)]/2

=> x = [-6 ±6√3]/2

=> x = -3[1 ± √3]

• Login to reply the answers
• Glipp
Lv 7
7 years ago

(r - 3)(r + 9) = -9

r^2 + 6r - 27 = -9

r^2 + 6r + 9 = 27

(r + 3)^2 = 27

r + 3 = ±3√3

r = -3 ± 3√3

r = -3(1 ± √3)

• Login to reply the answers
• Anonymous
7 years ago

You have to put it all on one side and then expand. That will make it easier for you to use the formula. Here is a hint: expanded form is r squared + 6r - 18 = 0.

• Login to reply the answers
• Adam
Lv 5
7 years ago

This link has a step by step solution to your problem:

http://www.symbolab.com/solver/quadratic-equation-...

Hope this helps

• Login to reply the answers
Still have questions? Get your answers by asking now.